MANAGING HYPOMINERALIZATION IN FIRST PERMANENT MOLARS: DIAGNOSIS TO TREATMENT APPROACHES - Cosmin Gabriel Popa; Ioana Mârțu; Emanuela Crăciunescu; Diana Diaconu-Popa; Galina Pancu; Alexandra Jităreanu; Doriana Agop Forna; Oana Bejan; Carmen Savin (Romanian Society of Oral Rehabilitation, 2024)
The concept "Molar Incisor Hypomineralization" (MIH) was introduced in 2001 to specify enamel hypomineralization impacting one or more permanent first molars, commonly accompanied by the involvement of one or more permanent incisors. The severity of carious lesions can be influenced and exacerbated by alterations in the structure of enamel and dentin. Consequently, MIH syndrome (Molar Incisor Hypomineralization syndrome) may pose a significant health concern for pediatric, adolescent, and young adult patients, as well as their tutors or caregivers, and for both pediatric and general dental practitioners. MIH syndrome is gaining considerable attention amongst worldwide clinicians and pediatric dentists as a result of its extensive clinical impact on oral health and quality of life and its various consequences (immediate, medium and long term) on the dental arch development, occlusion and psychological impact on the pediatric patient.